Variability in modern pollen rain from moist and wet tropical forest plots in Ghana, West Africa. Issue 1 (2nd January 2019) - Julier, Adele C. M.; Jardine, Phillip E.; Adu-Bredu, Stephen; Coe, Angela L.; Fraser, Wesley T.; Lomax, Barry H.; Malhi, Yadvinder; Moore, Sam; Gosling, William D.
Abstract: How pollen moves within and between ecosystems affects factors such as the genetic structure of populations, how resilient they are to environmental change, and the amount and nature of pollen preserved in the sedimentary record. We set artificial pollen traps in two 100 m by 100 m vegetation plots, one in a wet evergreen forest, and one in a moist semi-deciduous forest in Ghana, West Africa. Five traps from each plot were counted annually from 2011 to 2014, to examine spatial and temporal variation in the pollen rain of the most abundant taxa shared between pollen and vegetation assemblages. Samples from the wet evergreen plot exhibited high variability within years, with the dominant pollen types changing between samples, and many pollen taxa being over-represented relative to their parent plant abundance in some traps whilst being entirely absent from others. The most abundant plant taxa of the wet evergreen plot ( Drypetes and Cynometra ) do, however, constitute major components of the pollen rain. There is less variation between samples from the moist semi-deciduous plot spatially, as it is dominated by Celtis, which typically comprises >70% of the pollen assemblages. We conclude that pollen rain in these tropical ecosystems is highly heterogeneous, and suggest that pollen assemblages obtained by trapping are susceptible to small-scale variations in forest structure. Conversely, this may mean that current recommendations of more than three years of trapping in tropical systems may be too high, and that space could substitute for time in modern tropical pollen trapping.